Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1042/bj2370131
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory role for polyamines in protein kinase C activation and insulin secretion in mouse pancreatic islets

Abstract: The occurrence and function of polyamines in protein kinase C activation and insulin secretion in mouse pancreatic islets were studied. Determination of polyamines in mouse islets revealed 0.9 +/- 0.3 (mean +/- S.E.M., n = 6) pmol of putrescine, 11.7 +/- 3.2 (8) pmol of spermidine and 3.7 +/- 0.6 (8) pmol of spermine per islet, corresponding to intracellular concentrations of 0.3-0.5 mM-putrescine, 3.9-5.9 mM-spermidine and 1.2-1.9 mM-spermine in mouse islets. Stimulation of insulin secretion by glucose, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 36 publications
(39 reference statements)
2
30
1
Order By: Relevance
“…However, polyvalent cations, such as magnesium (Mg ), and polycationic compounds, such as polyamines, have been used in other cell systems to activate the CaR (40-42). In pancreatic islets, spermine inhibits glucoseinduced insulin-secretion (43), whereas spermidine and putrescine, which are less potent agonists of the CaR (42), had no effect on glucose-induced secretion. We have previously shown that polymyxin B, another polyamine, has a profound inhibitory effect on insulin secretion (44), whereas the inhibitory action of the divalent cation Co 2 + can be dissociated from any inhibition of Ca 2 + i n flux (45) and, thus, is consistent with activation of the CaR.…”
Section: Discussionmentioning
confidence: 99%
“…However, polyvalent cations, such as magnesium (Mg ), and polycationic compounds, such as polyamines, have been used in other cell systems to activate the CaR (40-42). In pancreatic islets, spermine inhibits glucoseinduced insulin-secretion (43), whereas spermidine and putrescine, which are less potent agonists of the CaR (42), had no effect on glucose-induced secretion. We have previously shown that polymyxin B, another polyamine, has a profound inhibitory effect on insulin secretion (44), whereas the inhibitory action of the divalent cation Co 2 + can be dissociated from any inhibition of Ca 2 + i n flux (45) and, thus, is consistent with activation of the CaR.…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol esters, which activate protein kinase C, inhibit the L-type channel current in this preparation (Linden & Routtenberg, 1989). Putrescine is known to inhibit protein kinase C but does not affect the cyclic AMP-dependent protein kinase (Qi, Schatzman, Mazzei, Turner, Raynor, Liao & Kuo, 1983;Thams, Capito & Hedeskov, 1986;Moruzzi, Barbiroli, Monti, Tadolini, Hakim & Mezzetti, 1987). It was therefore hypothesized that the effect of putrescine might be mediated via protein kinase C.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme, in various tissues, was found to be inhibited by spermine, non-competitively with respect to Ca2 and PS (Qi et al, 1983). The activation of protein kinase C, from mouse pancreatic islets, by a phorbol ester [tetradecanoylphorbol acetate (TPA)], PS and Ca2", was also inhibited by spermine or spermidine (Thams et al, 1986). This effect, which was correlated at the cellular level with a decreased insulin secretion, was attributed to a competition between polyamines and Ca'2 for the PS domain in the membrane which binds the kinase.…”
Section: Polyamines and Transportmentioning
confidence: 99%